Measurement of N2O emissions over the whole year is necessary for estimating reliable emission factors. (April 2020) - Shang, Ziyin; Abdalla, Mohamed; Kuhnert, Matthias; Albanito, Fabrizio; Zhou, Feng; Xia, Longlong; Smith, Pete
Abstract: Nitrous oxide emission factors (N2 O-EF, percentage of N2 O–N emissions arising from applied fertilizer N) for cropland emission inventories can vary with agricultural management, soil properties and climate conditions. Establishing a regionally-specific EF usually requires the measurement of a whole year of N2 O emissions, whereas most studies measure N2 O emissions only during the crop growing season, neglecting emissions during non-growing periods. However, the difference in N2 O-EF (ΔEF) estimated using measurements over a whole year (EFwy ) and those based on measurement only during the crop-growing season (EFgs ) has received little attention. Here, we selected 21 studies including both the whole-year and growing-season N2 O emissions under control and fertilizer treatments, to obtain 123 ΔEFs from various agroecosystems globally. Using these data, we conducted a meta-analysis of the ΔEFs by bootstrapping resampling to assess the magnitude of differences in response to management-related and environmental factors. The results revealed that, as expected, the EFwy was significantly greater than the EFgs for most crop types. Vegetables showed the largest ΔEF (0.19%) among all crops (0.07%), followed by paddy rice (0.11%). A higher ΔEF was also identified in areas with rainfall ≥600 mm yr −1, soil with organic carbon ≥1.3% and acidic soils. Moreover, fertilizer type, residue management, irrigation regime and duration of the non-growing season were other crucial factors controlling the magnitude of the ΔEFs. We also found that neglecting emissions from the non-growing season may underestimate the N2 O-EF by 30% for paddy fields, almost three times that for non-vegetable upland crops. This study highlights the importance of the inclusion of the non-growing season in the measurements of N2 O fluxes, the compilation of national inventories and the design of mitigation strategies. Graphical abstract: Image 1 Highlights: Whole year N2 O emission factors (EFs) were generally greater than growing season EFs. Excluding difference between whole year and growing season lowered the EF by 30% for paddy rice. Excluding the difference lowered the EF by 10% for non-vegetable crops. Higher difference found in areas with rainfall ≥600 mm yr −1, SOC ≥1.3% and pH < 7. Abstract : Fallow-season N2 O emissions must be included when calculating emission factors (EFs); neglecting them lowers the EFs by 30% for paddy rice and 10% for non-vegetable crops.